2017
DOI: 10.1002/jrsm.1279
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new method for librarian‐mediated literature searches for systematic reviews

Abstract: ObjectiveTo evaluate and validate the time of completion and results of a new method of searching for systematic reviews, the exhaustive search method (ESM), using a pragmatic comparison.Methods: Single-line search strategies were prepared in a text document. Term completeness was ensured with a novel optimization technique. Macros in MS Word converted the syntaxes between databases and interfaces almost automatically. We compared search characteristics, such as number of search terms and databases, and outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 14 publications
0
48
0
Order By: Relevance
“…Research has shown that translators should take care because interface differences can impact on retrieval (Damarell et al, 2013;Neyt & Chalon, 2013). Authors have also provided algorithms (macros) to automate the conversion of search strategies between interfaces (Bramer, Rethlefsen, Mast & Kleijnen, 2017). However, despite this information, we suspect that the impact and performance of such translations are rarely investigated in-depth because simple conversion is already a time-consuming process (Bramer et al, 2017).…”
mentioning
confidence: 99%
“…Research has shown that translators should take care because interface differences can impact on retrieval (Damarell et al, 2013;Neyt & Chalon, 2013). Authors have also provided algorithms (macros) to automate the conversion of search strategies between interfaces (Bramer, Rethlefsen, Mast & Kleijnen, 2017). However, despite this information, we suspect that the impact and performance of such translations are rarely investigated in-depth because simple conversion is already a time-consuming process (Bramer et al, 2017).…”
mentioning
confidence: 99%
“…While not yet at industrial levels of production, the papers in this Special Issue, dominated by multi‐author and multidisciplinary work, attest to the demise of the information retrieval “cottage industry”. Collaborations span institutions and the academic‐commercial divide . Academic review organizations (eg, ScHARR, PenTag, and YHEC) and health technology agencies (eg, CADTH) and networks (such as Cochrane , and the Medical Library Association collaboration) continue to play a critical part.…”
Section: Goodbye To Cottage Industriesmentioning
confidence: 99%
“…This accurately captures the prevailing zeitgeist for systematic review efficiency and rapid review methods. Efficiencies are claimed for search strategy construction, randomized controlled trial (RCT) screening, and for searching for protocols, and all three authorial teams provide empirical evidence to support their claims. Such efficiencies must be accompanied by robust quality assurance procedures; for one of which, peer review of search strategies, we now have important supplemental evidence of benefit …”
Section: Goodbye To Cottage Industriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Two contributions address two of the most important overarching issues for information retrieval in evidence synthesis, namely, the efficiency and quality of our practice. Bramer and colleagues consider innovative ways of interrogating traditional bibliographic databases by evaluating librarian‐mediated single‐line search strategies in terms of precision and time taken to search …”
mentioning
confidence: 99%